2020
DOI: 10.1007/s11442-020-1736-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of farmland expansion on drought over the past century in Songnen Plain, Northeast China

Abstract: The effects of human activities on climate change are a significant area of research in the field of global environmental change. Land use and land cover change (LUCC) has a greater effect on climate than greenhouse gases, and the effect of farmland expansion on regional drought is particularly important. From the 1910s to the 2010s, cultivated land in Songnen Plain increased by 2.67 times, the area of cultivated land increased from 4.92×10 4 km 2 to 13.14×10 4 km 2 , and its percentage of all land increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Uncertainty for soil matrix mainly resulted from soil texture, that is, less clay in soils was accompanied by more aggregate protection in broadleaved forests as compared to that in coniferous forest. In Northeast China, soil texture with more clay is mainly found in the central region of Songnen Plain (HLJTR-Editorial-Committee, 1992) (e.g., Dumeng site in this study) and is dominated by croplands and grasslands with limited forests (Yu et al, 2020). The forest-dominated regions (Daxinganling Mts., Xiaoxinganling Mts., and Changbai Mts.…”
Section: Uncertainty From Geo-climatic Conditions Soil Matrix Andmentioning
confidence: 88%
“…Uncertainty for soil matrix mainly resulted from soil texture, that is, less clay in soils was accompanied by more aggregate protection in broadleaved forests as compared to that in coniferous forest. In Northeast China, soil texture with more clay is mainly found in the central region of Songnen Plain (HLJTR-Editorial-Committee, 1992) (e.g., Dumeng site in this study) and is dominated by croplands and grasslands with limited forests (Yu et al, 2020). The forest-dominated regions (Daxinganling Mts., Xiaoxinganling Mts., and Changbai Mts.…”
Section: Uncertainty From Geo-climatic Conditions Soil Matrix Andmentioning
confidence: 88%
“…Due to the high concentration of grassland, animal husbandry is also very developed in the Songnen Plain. The climate of the Songnen Plain is a temperate monsoon climate with four distinct seasons, and it is a semi-humid and semi-arid zone [51]. The average annual temperature increases gradually from north to south, with a latitudinal distribution.…”
Section: Study Areamentioning
confidence: 99%
“…In the short term, overgrazing and the reclamation of cultivated land will reduce the biomass and species diversity of grassland plant communities and have a negative impact on the restoration of ecological communities [52]. Yu et al [28], studying the impact of cultivated land expansion on drought in the Songnen Plain, also showed that the expansion of the cultivated land area destroys vegetation communities, increases the rate of grassland degradation, and indirectly affects the regional climate [53]. This trend slowed down after the implementation of the policy of returning farmland to forest and grassland in Northeast China in 2010, and the area of sandy land also decreased.…”
Section: Dynamic Change Relationship Of the Vegetation-lake-sand Land...mentioning
confidence: 99%
“…Spatial analysis, the MEDALUS model [28], the residual trend method [29], and other means have been employed to investigate the comprehensive impacts of vegetation, sandy landscape changes, climate factors, and human activities on landscape evolution [30]. Although vegetation and sandy landscapes are more sensitive to climate factors, human activities reduce this sensitivity.…”
Section: Introductionmentioning
confidence: 99%